AN ASSESSMENT OF PRIVACY REGIME IN BANGLADESH: A LEGAL ANALYSIS (UUM Journal of Legal Studies, 2022)
Privacy is one of the most valued human rights in the information age. Due to the present digital world context, privacy appears as one of the pressing problems. In a data-driven world, a vast majority of works are going online using personal data. Personal data emerge as the new fuel to the Internet, and coin to the digital world. This digital atmosphere makes life easier, faster, and smarter, while simultaneously posing tremendous challenges to privacy. Therefore, the debate encompassing privacy evolves as one of the hot-button issues in contemporary world policies, politics, and business. In response, multiple policy measures have been adopted at national, regional, and international levels. To cope with this global trend, establish a safer online ecosystem, and secure citizens’ right to privacy, Bangladesh should maintain an adequate privacy protection regime. This landscape leads the current researcher to explore and assess the privacy protection regime of Bangladesh, as there is a lack of research in this area. There is a clear gap in the existing literature that requires to be filled in, and this research aimed to fill that gap using doctrinal legal research. The findings revealed that privacy was not adequately protected in Bangladesh due to, mainly, the lack of omnibus data privacy legislation. This article concluded by offering some workable suggestions, and especially, urged for enacting comprehensive data protection legislation in Bangladesh. Presumably, this research will enlighten all stakeholders regarding an overall picture of the privacy protection regime of Bangladesh. Moreover, this study will facilitate relevant stakeholders to map their future strategies and policy directions towards establishing an effective privacy protection regime in Bangladesh.